Urban Mobility, Tourism, and Liveability in Penang: Anticipated Benefits of the Proposed Light Rail Transit (LRT) System - Goh Wei Siang; Sulong, Amri; Raja Nor Azuwah Raja Yusof (Journal of Humanistic, Management and Social Science Review, 2025)
Penang Island, Malaysia, continues to grapple with persistent urban challenges, including severe traffic congestion, constrained public transport accessibility, and growing environmental concerns. In response, the Penang state government has proposed a Light Rail Transit (LRT) system under the Penang Transport Master Plan (PTMP) to address these critical issues. This conceptual paper examines the potential urban benefits of the proposed LRT project, with a particular emphasis on its capacity to reduce traffic congestion, strengthen the tourism sector, and enhance urban liveability. Through the analysis of secondary data, regional infrastructure trends, and comparative insights from established LRT systems in Southeast Asian cities, the study highlights the anticipated socio-economic, environmental, and mobility-related impacts of the project. The findings suggest that, if effectively planned and implemented, the Penang LRT system could play a transformative role in fostering a more sustainable, connected, and inclusive urban environment, contributing positively to the island’s long-term economic growth and quality of life.